(untitled) - Ghezzi, Carlo (Upper Saddle River, N.J., 2003)
Appropriate for both undergraduate and graduate introductory software engineering courses found in Computer Science and Computer Engineering departments. This text provides selective, in-depth coverage of the fundamentals of software engineering by stressing principles and methods through rigorous formal and informal approaches. The authors emphasize, identify, and apply fundamental principles that are applicable throughout the software lifecycle, in contrast to other texts which are based in the lifecycle model of software development. This emphasis enables students to respond to the rapid changes in technology that are common today.
Keywords: Software engineering,Kỹ thuật phần mềm